Forms of Implementation of the Philosophy of Science in the Development of Educational Science Theoretically and Practically - Annisa Maulida Ramadhani; Sofyan Sauri (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to explain the implementation of the philosophy of science in the development of educational science, using literature review and qualitative descriptive methods in its presentation. The results obtained are: (1) Development of educational science which grows based on the scope of the philosophy of science, namely science (ontology), how the process of acquiring knowledge is (epistemology), and how the benefits of science are (axiology). (2) There are two approaches to the philosophy of science in educational research, namely the positivistic and non-postivistic approaches. The positivistic approach focuses on observation and experience as a form of searching for new truths, while the non-positivistic approach is a method that is not influenced by observation and experience, cannot be measured, and can be proven without observation. (3) Implementation of the philosophy of science in theoretical and practical aspects which are interrelated, theoretically producing a well-organized and systematic branch of science. Practically, it produces a humanistic and social spirit, namely a form of empathy with the hope that the knowledge taught can be useful in the realities of human life.